230k views
0 votes
X^-2+4x^-1+3=0 solve by making appropriate substitution

1 Answer

5 votes

ANSWER


x = - 1 \: or \: x = - (1)/( 3)

Step-by-step explanation

The given equation is:


{x}^( - 2) + 4 {x}^( - 1) + 3 = 0

Recall that:


{a}^( - m) = \frac{1}{ {a}^(m) }


\frac{1}{ {x}^(2) } + (4)/(x) + 3 = 0

Or


{( (1)/(x) )}^(2) + 4( (1)/(x) ) + 3 = 0

Let


u = (1)/(x)

Our equation then becomes:


{u}^(2) + 4u + 3 = 0

The factors of 3 that add up to 4 are:


{u}^(2) + 3u + u + 3


u(u + 3) + 1(u + 3) = 0


(u + 1)(u + 3) = 0


u + 1 = 0 \: or \: u + 3 = 0


u = - 1 \: or \: u = - 3

This implies that:


(1)/(x) = - 1 \: or \: (1)/(x) = - 3


x = - 1 \: or \: x = - (1)/( 3)

User Sznrbrt
by
6.0k points